Characterization of socio-land management modes of lowland areas in the Kyon municipality (Burkina Faso) - Yaya MAIGA; Yanogo P. I. (African Journal on Land Policy and Geospatial Sciences)
Context and background The mastery and control of rural areas remain a challenge for both landowners and the Burkinabe State. The major agricultural production basins, particularly areas with high exploitation of lowlands, experience permanent changes in production actors and land management strategies. This leads to the establishment of a multitude of access and exploitation rules aimed at better controlling all production chains. Therefore, what are the set of rules and principles that govern the exploitation of lowland in the study area? What are the changes in the management principles that govern the exploitation of lowland in the study area? What are the explanatory factors for this observed dynamic? Goal and Objectives: The main objective of this study is to analyze the different modes of social and land management of wetland landscapes in Kyon municipality (Burkina Faso). Methodology: The study is based on both quantitative and qualitative research methodologies. A total of 378 producers were surveyed using individual questionnaires. In addition, individual interviews were conducted with landowners and resource persons, as well as group interviews with some solidarity groups of producers Results: